Potensi dan Strategi Marketing Perbankan Syariah pada Segmen Kelas Menengah Indonesia - Rizal, Sofyan (Al-Iqtishad: Journal of Islamic Economics, 2013)
Group of middle-class society is a tremendous market for Islamic business, especially Islamic banking. The fact that the majority of Indonesias population is Muslim, Islamic business institutions should work on the mid-market segment earnestly. The potential of middle class development in Indonesia gives an opportunity for Islamic banks to compete in the market. Various characteristics of the middle class used as a valuable input in conducting market segmentation, targets, and formulate strategies to create the accepted products.DOI: 10.15408/aiq.v5i2.2116